Механічні характеристики трифазних асинхронних двигунів при однофазному живленні - Маляр, Василь Сафронович; Маляр, Андрій Васильович (НТУ "ХПІ", 2016)
Запропоновано метод розрахунку механічних характеристик трифазних асинхронних двигунів, які живляться від однофазної мережі. Обертове магнітне поле створюється завдяки вмиканню послідовно в одну фазу конденсаторів. Задача розв’язується як крайова у трифазній нерухомій системі координат. В математичній моделі двигуна враховується насичення магнітопроводу та витіснення струму.

Aim. Development of a method for calculating mechanical characteristics of three-phase induction motors with single-phase power supply. Methods. The developed algorithm is based on the high-adequacy mathematical model of motor and projection method for solving the boundary problem for equations of electrical circuits balance presented in the three-phase coordinate system. As a result of asymmetry of power supply to the stator windings, in steady state, flux-linkage and current change according to the periodic law. They are determined by solving the boundary problem. Results. The developed mathematical model allows determining periodic dependence of coordinates as a function of slip and, based on them, mechanical characteristics of motors. Academic novelty. The developed method relies on a completely new mathematical approach to calculation of stationary modes of nonlinear electromagnetic circuits, which allows obtaining periodic solution in a timeless domain. Practical value. Using the developed calculation algorithm, one can select capacitance required to start an induction motor with single-phase power supply and calculate static mechanical characteristics at a given capacitance.
Mechanical characteristics of three-phase induction motors with single-phase power supply
Keywords: крайова задача; проекційний метод; конденсатор; електромагнітний момент; mechanical characteristic; induction motor; boundary problem; projection method; capacitor